Advances in CAR-T Cell Genetic Engineering Strategies to Overcome Hurdles in Solid Tumors Treatment - Andrea, Alain E.; Chiron, Andrada; Mallah, Sarah; Bessoles, Stéphanie; Sarrabayrouse, Guillaume; Hacein-Bey-Abina, Salima (Frontiers in Immunology, 2022)
During this last decade, adoptive transfer of T lymphocytes genetically modified to express chimeric antigen receptors (CARs) emerged as a valuable therapeutic strategy in hematological cancers. However, this immunotherapy has demonstrated limited efficacy in solid tumors. The main obstacle encountered by CAR-T cells in solid malignancies is the immunosuppressive tumor microenvironment (TME). The TME impedes tumor trafficking and penetration of T lymphocytes and installs an immunosuppressive milieu by producing suppressive soluble factors and by overexpressing negative immune checkpoints. In order to overcome these hurdles, new CAR-T cells engineering strategies were designed, to potentiate tumor recognition and infiltration and anti-cancer activity in the hostile TME. In this review, we provide an overview of the major mechanisms used by tumor cells to evade immune defenses and we critically expose the most optimistic engineering strategies to make CAR-T cell therapy a solid option for solid tumors.